Tuning the wrinkling patterns of an interfacial/coating layer via a regulation interphase. (1st January 2017) - Gao, Chao; Li, Yaning
Abstract: In this investigation, the mechanical response of a tri-phase system subjected to far-field compression is explored. The system includes a stiffer interfacial/coating layer surrounded by an interphase/regulation layer, and both layers are embedded in an infinite softer matrix. Both theoretical and finite element (FE) mechanical models of the system are developed. From the results of these models, three wrinkling patterns are proved to exist: (I) single-layer wrinkling mode, (II) bi-layer wrinkling mode, and (III) the simultaneous nested-wrinkling mode. The wrinkling patterns are reported to be attributed to the instability of the system. The results of FE simulations show that the theoretical model can accurately predict the instability of the system. The influences of the geometry and material properties of all three phases on the transition between the three instability modes are quantified. It reveals that the regulation layer/interphase around the interfacial/coating layer is the key to tune the wrinkling patterns. The critical physical parameters to determine the characteristics of the three instability modes are the effective thickness ratio between the regulation layer and interfacial/coating layer, the effective stiffness ratio between the interfacial/coating layer and the regulation layer and that between the interfacial/coating layer and the matrix. As an example of the application of the theoretical model, a graded interfacial wrinkling pattern is designed and verified via FE simulations.